Building Ethical and Socially Insightful Graduates Through Civic Education to Face Professional Challenges in the Era of Globalization - Radhita Maharani Ramli; Khamim Zarkasih Putro (Penerbit Hellow Pustaka, 2025)
The era of globalization demands college graduates who not only have professional skills, but also strong ethics and broad social insight. This article discusses the role of Civic Education in forming ethical and socially aware graduates to face professional challenges amidst global competition. Through Civic Education, students are equipped with an understanding of moral values, social responsibility, and critical thinking skills. They are also taught to appreciate diversity and adapt to technological developments and global issues. In addition, this program strengthens students' abilities in making ethical and solution-oriented decisions regarding social problems. With a dynamic and interactive learning approach, Civic Education contributes to producing graduates who are not only academically competent, but also able to bring positive impacts to society in the era of globalization.